Reconstructing the past : history of municipality, city, and provincial libraries in the province of Rizal from 1951 to 2018 - Guilles, Dennis Marco T.
This study focused on the narrative description of historical facts, formulated acceptable interpretations, and established clear connections of what happened in the past based on factual and concrete evidence, to better understand the present conditions of public libraries in Rizal province. Arguably, if librarians were able to fully understand their libraries' present conditions, then they would be able to make informed decisions and execute action plans towards growth and development of their respective libraries.